A Range Free Localization Method for Overlapped Optical Attocells Using Neighbor S Information - Soto-Gomez, J; Adasme-Soto, P; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper we present a novel range free method based on connectivity and network architecture information. Optical attocells deployed within an indoor scenario send periodically its own position information as well as neighbor s information. The mobile node (MN) uses this information in order to self-determine its position. A square 5 × 5(m) room with 9 LED lights placed equidistant in the ceiling is modeled as the proposed scenario. Our method is compared with two traditionally used algorithms in terms of accuracy and error dispersion. Numerical results show that the proposed method outperforms the traditional methods in the both proposed metrics. © 2018 IEEE.